ТИПОЛОГІЯ СТОСУНКІВ НА КУРСАХ ПІДВИЩЕННЯ КВАЛІФІКАЦІЇ ВЧИТЕЛІВ (Педагогіка вищої та середньої школи, 2008)
The authors define différent approaches to the notion of relations’ typology and ways of forming them in the process of the improvement of professional teachers’ skill.